Asking questions of nature: Art as a catalyst for ecological consciousness - Patrick M. Lydon (Nature-Based Solutions)
The challenge of breaking through preconceived societal norms and narratives is a common hurdle in advocating for transformative ideas. Cultural conditioning and the expectations placed on individuals and institutions are powerful forces, and they often keep new ways of seeing — and ideas like Nature-Based Solutions (NBS) — trapped in conventional patterns of thought and behavior. This paper suggests alternatives for connecting to these alternative ways of seeing through artist-led exhibitions and interventions that not only ask questions of nature, but also allow nature to ask questions of us. We look at five projects by City as Nature studio, including “Forest is the Artist” an exhibition which gives agency to a Korean forest, and a concept restaurant “World's Slowest Restaurant” where the artist makes customers wait for 6–8 weeks for their meal to be grown. Common to all of the artworks explored in this paper, is the view of nature as a partner. This view allows us to start from an acknowledgment of the human disconnect from nature, and proceed to explore the transformative potential of mending this disconnect by collaborating directly with nature in various ways. To achieve this, we use art as a way of giving human beings new stories, new spaces, and new social permissions that allow us to question norms and explore our own connection to the natural world. The outcomes suggest that the process of seeing ourselves as “ecological beings” does not necessarily require complex or elaborate interventions, but merely the opportunity to pause, reflect, and interact with the world in more profound ways. Through the views, examples, and outcomes in this paper, we find simple methods available to both scientists and the public alike, that can help us adopt more sustainable and meaningful ways of seeing. A valuable perspective for NBS professionals, this paper also highlights how the success of NBS is tied not only to quantitative results, but also to each individual's ability to foster real relationships, a sense of belonging, awe, and reverence for and with all of nature. It also suggests that this is achievable.